Deformation behavior and mechanical properties of polycrystalline and single crystal alumina during nanoindentation - Mao, W.; Shen, Y.; Lu, Chungsheng (Elsevier, 2011)
The nanoscale pop-in phenomena in polycrystalline alpha-Al2O3 and single crystal alpha-Al2O3(0001) were comparatively investigated by nanoindentation with Berkovich indenters. It was found that different radii and loading rates have significant effects on the pop-ins formation, stress distributions and dislocation nucleations. Using the Hertzian contact theory and energetic model approach, the pop-in observations and resolved shear stress analysis are consistent with the explanation that the first pop-in corresponds to the nucleation of homogeneous dislocations when the theoretical shear strenghth is exceeded.